2004
DOI: 10.1093/sleep/27.2.324
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic Method for Scoring Leg Movements in Polygraphic Sleep Recordings and Its Validity in Comparison to Visual Scoring

Abstract: The degree of accordance between the 2 visual scorings and between the visual and the automatic scorings were comparable. Therefore, this method is valid and may be used for the automatic detection of leg movements in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Inter‐rater and inter‐clinical variability has been evaluated on sleep staging (Danker‐Hopfe et al., ; Rosenberg & Van Hout, ; Younes et al., ) and on respiratory events (Rosenberg & Van Hout, ). Concerning motor events during sleep, previous studies have always included experts trained homogenously to evaluate inter‐rater reliability, thus excluding inter‐clinical variability (Bliwise et al., , ; Wetter et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inter‐rater and inter‐clinical variability has been evaluated on sleep staging (Danker‐Hopfe et al., ; Rosenberg & Van Hout, ; Younes et al., ) and on respiratory events (Rosenberg & Van Hout, ). Concerning motor events during sleep, previous studies have always included experts trained homogenously to evaluate inter‐rater reliability, thus excluding inter‐clinical variability (Bliwise et al., , ; Wetter et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The visual identification of MEs is time consuming and subjective, because scoring rules are not uniquely interpretable (Iber et al., ). Studies on inter‐rater agreement have shown that, although experts tend to agree up to a level of 95% on LM identification and the PLMS index (Bliwise et al., ; Wetter et al., ), lower agreements are seen in identification of tonic and phasic EMG activities, which characterize RSWA, with identification of tonic activities being the one with the lowest agreement among experts (Bliwise et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no effort made in this study to compare results between these, partly because each program has somewhat different concepts. The two oldest methods by Tauchmann and Pollmächer (13) and Wetter et al (14) were written in JAVA and did not use the current WASM criteria. The Ferri et al (15) was the first program to apply the basic concept of two thresholds (onset and offset of events) used in the WASM criteria, but they used fixed values for the thresholds for all records checking to ensure the resting EMG was at 2 μv for their recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Although the standard procedure for scoring and counting of PLMS is still based on visual criteria [11], Wetter and co-workers [12] have developed an automatic method for PLMS scoring in polysomnography, and demonstrated its high agreement with visual scoring performed by welltrained scorers. A recent study looked into the correlation between rating scales and sleep laboratory measurements [13], and showed a significant correlation between subjective (International RLS Severity Scale; IRLS) and objective (PLMS and derived measures) parameters in patients with RLS.…”
Section: Diagnostic Criteria and Instrumentsmentioning
confidence: 99%